Download Presentation
## POLYNOMIALS

- - - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - - -

**TOPICS COVERED**• Polynomials in One Variable • Zeroes of a polynomial • Remainder Theorem • Factor Theorem • Algebraic Identities**Introduction**An algebraic expression in which variables involved have only non-negative integral powers is called a polynomial. E.g.- (a) 2x3–4x2+6x–3 is a polynomial in one variable x. (b) 8p7+4p2+11p3-9p is a polynomial in one variable p. (c) 4+7x4/5+9x5 is an expression but not a polynomial since it contains a term x4/5, where 4/5 is not a non-negative integer.**In the polynomial x2 + 2x, the expressions x2 and 2x are**called the terms of the polynomial. • Similarly, the polynomial 3y2 + 5y + 7 has three terms, namely, 3y2, 5y & 7. • Example : –x3 + 4x2 + 7x – 2. This polynomial has 4 terms, namely, –x3, 4x2, 7x and –2. Each term of a polynomial has a coefficient.So, in –x3 + 4x2 + 7x – 2, the coefficient of x3 is –1, the coefficient of x2 is 4, the coefficient of x is 7 and –2 is the coefficient of x0. (Remember, x0 = 1) • The coefficient of x in x2 – x + 7 is –1.**Examples of Polynomials in one variable**• Algebraic expressions like 2x, x2 + 2x, x3 – x2 + 4x + 7 have only whole numbers as the exponents of the variable. Expressions of this form are called polynomials in one variable. In the examples above, the variable is x. • 3y2 + 5y is a polynomial in the variable y. • t2 + 4 is a polynomial in the variable t.**Degree of a Polynomial in one variable.**• What is degree of the following binomial? The answer is 2. 5x2 + 3 is a polynomial in x of degree 2. In case of a polynomial in one variable, the highest power of the variable is called the degree of polynomial.**Degree of a Polynomial in two variables.**• What is degree of the following polynomial? • The answer is five because if we add 2 and 3 , the answer is five which is the highest power in the whole polynomial. E.g.- is a polynomial in x and y of degree 7. In case of polynomials on more than one variable, the sum of powers of the variables in each term is taken up and the highest sum so obtained is called the degree of polynomial.**Polynomials in one variable**The degree of a polynomial in one variable is the largest exponent of that variable. A constant has no variable. It is a 0 degree polynomial. This is a 1st degree polynomial. 1st degree polynomials are linear. This is a 2nd degree polynomial. 2nd degree polynomials are quadratic. This is a 3rd degree polynomial. 3rd degree polynomials are cubic.**Examples**Text Txt Text Text Text**QUESTIONS**• Which of the following expressions are polynomials in one variable and which are not ? • i) 4x ²-3x+7 ii) y+2/y • Classify the following as linear ,quadratic and cubic polynomials : • i)x ²+x ii)y+y ²+4 iii)1+x iv)3t vi)t²**Zeroes of a Polynomial**A zero of a polynomial p(x) is a number c such that p(c)=0. Example: Q-Check whether -2 and +2 are the zeroes of the polynomial x+2? ANS-Let p(x)=x+2 Then p(2)=2+2=4, p(-2)=(-)2 +2=0 Therefore -2 is a zero of the polynomial but +2 is not.**QUESTIONS**• Find the value of the polynomial 5x-4x²+3 at i)x=0 ii) x= (-1) (iii)x=2 • Solutions: • (i) p(x) =5x-4x²+3 • p(0) =5(0)-4(0)2+3=0-0+3=3 • ii) p(-1)=5(-1)-4(-1)2+3 = -5-4+3 = -6 • iii) p(2) =5(2)-4(2)2+3 =10-16+3 = -3**QUESTIONS**• Verify whether the following are zeroes of the polynomials . • i)p(x) =3x+1 ,x =(-1/3) • Sol :p(x) =3x+1 • p(-1/3) =3(-1/3) +1 = -1+1 =0 • ∴ x= (-1/3) is the zero of 3x+1. • ii) p(x) = (x+1) (x-2) ,x =-1 ,2 • Sol : p(-1) =(-1+1)(-1-2) =0(-3)=0 • Since p(-1) =0 ,so x= -1 is a zero of p(x) . • p(2) = (2+1) (2-2) =3(0) =0 • So ,x=2 is a zero of p(x) .**QUESTIONS**• Find the zero of the polynomial in each of the following cases : • i)p(x) =x+5 • Sol : p(x) =x+5 • P(x)=0 ,x+5 =0 ,x= -5 • Thus ,a zero of (x+5 ) is (-5) • ii) p(x) =3x • P(x) =0 ,3x =0 ,x=0/3 =0 • Thus ,a zero of (3x) is 0 .**QUESTIONS FOR PRACTICE**• 1) Find p(0) ,p(1) ,p(2) for each of the following polynomials : • i)p(y) =y²-y+1 ii)p(t) =2+t+2t²-t³ • iii)p(x) =x³ iv) p(x) =(x-1) (x+1) • 2) Verify whether the following are zeroes of the polynomial . • i) p(x) =x²-1 ,x =1 , -1 • ii ) p(x) = 2x+1 ,x =1/2 • 3)Find the zero of the polynomial in each of the following cases : • i)p(x) =x-5 ii)p(x) =2x+5 iii)p(x) = 3x – 2 .**Remainder Theorem**Statement: Let p(x) be any polynomial of degree greater than or equal to one and let a be any real number. If p(x) is divided by the linear polynomial x – a, then the remainder is p(a). .**Proof : Let p(x) be any polynomial with degree greater than**or equal to 1. Suppose that when p(x) is divided by x – a, the quotient is q(x) and the remainder is r(x), i.e., p(x) = (x – a) q(x) + r(x) Since the degree of x – a is 1 and the degree of r(x) is less than the degree of x – a, the degree of r(x) = 0. This means that r(x) is a constant, say r. So, for every value of x, r(x) = r. Therefore, p(x) = (x – a) q(x) + r In particular, if x = a, this equation gives us p(a) = (a – a) q(a) + r = r, which proves the theorem**Examples**• Divide the polynomial 3x4 – 4x3 – 3x –1 by x – 1. Solution:By long division, we have:**Here, the remainder is – 5. Now, the zero of x – 1 is 1.**So, putting x = 1 in p(x), we see that p(1) = 3(1)4 – 4(1)³ – 3(1) – 1 = 3 – 4 – 3 – 1 = – 5, which is the remainder. • Find the remainder when x4 + x3 – 2x2 + x + 1 is divided by x – 1. Solution : Here, p(x) = x4 + x3 – 2x2 + x + 1, and the zero of x – 1 is 1. So, p(1) = (1)4 + (1)3 – 2(1)2 + 1 + 1= 2 So, by the Remainder Theorem, 2 is the remainder when x4 + x3 – 2x2 + x + 1 is divided by x – 1.**Practice questions**1.Find the remainder when x³+3x²+3x+1 is divided by i)x+1 ii)x-1/2 iii)x iv)x+л v)5+2x 2. Find the remainder when x³-ax²+6x-a is divided by x-a. 3.Check whether 7+3x is a factor of 3x³+7x.**Factor Theorem**Statement: If p(x) is a polynomial of degree n > 1 and a is any real number, then (i) x – a is a factor of p(x), if p(a) = 0, and (ii) p(a) = 0, if x – a is a factor of p(x). This actually follows immediately from the Remainder Theorem**Examples**• Examine whether x + 2 is a factor of x3 + 3x2 + 5x + 6 and of 2x + 4. Solution : The zero of x + 2 is –2. Let p(x) = x3 + 3x2 + 5x + 6 and s(x) = 2x + 4. Then, p(–2) = (–2)3 + 3(–2)2 + 5(–2) + 6 = –8 + 12 – 10 + 6 = 0**So, by the Factor Theorem, x + 2 is a factor of x3 + 3x2 +**5x + 6. Again, s(–2) = 2(–2) + 4 = 0 So, x + 2 is a factor of 2x + 4. In fact, it can also be checked without applying the Factor Theorem, since 2x + 4 = 2(x + 2).**Practice Questions**1.Determine whether x+1 is a factor of the following polynomials, x³-x²-(2+2)x+2 2. Find the value of k ,if x-1 is a factor of p(x) in each of the following cases: i)2x²+kx+2 ii)kx²-2x+1**Factorizing a Polynomial**Example: • Q-Factorisep(y)=y2 -5y +6 by using factor theorem. • Ans- factors of p(y), we find the factors of 6 factors of 6 are 1,2,3 Now, p(2)=22 -(5X2) +6=0 So, y-2 is a factor of p(y). Also, p(3)=32 –(5X3) +6=0 So y-3 is also a factor. Therefore, y2 -5y +6=(y-2) (y-3)**Practice Questions**1.factorize: i)12x² -7x+1 ii)2x²+7x+3 ii)6x²+5x-6 iv)3x²-x-4**Factorize: x³-23x²+142x-120**Soln: let p(x)=x³-23x²+142x-120 Factors of -120are: ± 1 ,±2,±3,±4,±5,±6,±8,±10,±12,±24,±30,±40,±60,±120. By hit and trial we get p(1)=0. so x-1 is a factor of p(x). Therefore p(x)=x³-x²-22x²+22x+120x-120 =x²(x-1)-22x(x-1)+120(x-1) =(x-1)(x²-22x+120) {taken (x-1) common} further x²-22x+120 can be factorized to = x²-12x-10x+120 =x(x-12)-10x(x-12) =(x-12) (x-10) Hence, p(x)=(x-1) (x-12) (x-10)**Practice Questions**Factorize: i) x³-2x²-x+2 ii) x³-3x²-9x-5 ii) x³+13x²+32x+20 iv) 2y³ +y²-2y-1**Algebraic Identities**An algebraic identity is an algebraic equation that is true for all values of the variables occurring in it. Identity I : (x + y)2 = x2 + 2xy + y2 Identity II : (x – y)2 = x2 – 2xy + y2 Identity III : x2 – y2 = (x + y) (x – y) Identity IV : (x + a) (x + b) = x2 + (a + b)x + ab**Practice Questions**1.Use suitable identities to find the product of i)(3x+4) (3x-5) ii)(y²+3/2)(y²-3/2) 2.Evaluate the following without multiplying directly. i)103x107 ii)95x96 iii)104x96 3.Factorise using appropriate identities: i)9x²+6xy+y² ii)4y²-4y+1 iii)x²-(y²/100)**Identity V: (x + y + z)2 = x2 + y2 + z2 + 2xy + 2yz + 2zx**(x + y + z)2 = x2 + y2 + z2 + 2xy + 2yz + 2zx Remark :We call the right hand side expression the expanded form of the left hand side expression. The expansion of (x + y + z)2 consists of three square terms and three product terms.**Identity V: (x + y + z)2 = x2 + y2 + z2 + 2xy + 2yz + 2zx**We shall compute (x + y + z)2 by using Identity I. Let x + y = t. Then, (x + y + z)2 = (t + z)2 = t2 + 2tz + t2 (Using Identity I) = (x + y)2 + 2(x + y)z + z2 (Substituting value of t) = x2 + 2xy + y2 + 2xz + 2yz + z2 = x2 + y2 + z2 + 2xy + 2yz + 2zx(Rearranging) So, we get the following identity: (x + y + z)2 = x2 + y2 + z2 + 2xy + 2yz + 2zx**Example:**Ques: Write (3a+4b+5c)2 in expanded form. Soln: comparing the given expression with (x+y+z) 2, we find that, x=3a, y=4b, z=5c. Therefore, using Identity V, we have (3a+4b+5c) 2 =(3a) 2+(4b) 2+(5c) 2+2(3a)(4b)+ 2(4b)(5c)+2(5c)(3a) =9a2+16b2+25c2+24ab+40bc+30ac.**EXAMPLE**Ques: Factorize 4x2 +y2+z2-4xy-2yz+4zx Ans: 4x2+y2+z2-4xy-2yz+4zx = (2x) 2 +(-y) 2+(z) 2+2(2x)(-y)+ 2(-y)(z)+2(2x)(z) = [2x+(-y)+z] 2 = (2x-y+z) 2**Practice Questions**1.Expand each of the following: i)(x+2y+4z)² ii)(2x-y+z)² iii)(3a-7b-c)² iv)[(1/4)a-(1/2)b+1]² 2.Factorize: i)2x²+y²+8z²-22xy+42yz-8xz ii) 4x²+9y²+16z²+12xy-24yz-16xz**Identity VI: (x + y)3 = x3 + y3 + 3xy (x+ y)**(x + y)3 = (x + y) (x + y)2 = (x + y)(x2 + 2xy + y2) =x( x2 + 2xy + y2) + y(x2 + 2xy + y2) = x3 + 2x2y + xy2 + x2y + 2xy2 + y3 = x3 + 3x2y + 3xy2 + y3 = x3 + y3 + 3xy(x + y) So, we get the following identity: (x + y)3 = x3 + y3 + 3xy (x+ y)**Identity VII: (x - y)3 = x3- y3-3xy (x- y)**Identity VI : (x + y)3 = x3 + y3 + 3xy (x+ y) By replacing y by –y in the Identity VI, we get Identity VII : (x - y)3 = x3- y3-3xy (x- y) = x3 – 3x2y + 3xy2 – y3**QUESTIONS**1) Write the following cubes in expanded form : i)(2x+1)³ =(2x)³+1³+3(2x)(1)[(2x)+1] =8x³+1+6x[2x+1] = 8x³+1+12x²+6x =8x³+12x²+6x+1 ii)(2a-3b)³ =(2a)³-(3b)³-3(2a)(3b)[(2a)-(3b)] = 8a³-27b³-18ab(2a-3b) =8a³-27b³- [36a²b-54ab²] =8a³-27b³-36a²b+54ab²**QUESTIONS**Evaluate the following using suitable identities: i)(99)³= (100-1)³ = (100)³-1³-3(100)(1)[100-1] =1000000-1-300[100-1] =1000000-1-30000+300 =1000300-30001=970299 ii)(102)³ =(100+2)³ =(100)³+(2)³+3(100)(2)[100+2] =1000000+8+600[100+2] =1000000+8+60000+1200 =1061208**QUESTIONS**Factorize: i)8a³+b³+12a²b+6ab² =(2a)³+(b)³+3(2a)²b+3(2a)(b)² =(2a+b)³=(2a+b)(2a+b)(2a+b) ii)8a³-b³-12a²b+6ab² =(2a)³-(b)³-3(2a)²(b)+3(2a)(b)² =(2a-b)³=(2a-b)(2a-b)(2a-b)**QUESTIONS**Verify: i)x³+y³=(x+y)(x²-xy+y²) ii)x³-y³=(x-y)(x²+xy+y²) SOLN: i)RHS=(x+y)(x²-xy+y²) =x(x²-xy+y²)+y(x²-xy+y²) =x³-x²y+xy²+x²y-xy²+y³ =x³+y³ =LHS ii)RHS=(x-y)(x²+xy+y²) =x(x²+xy+y²)-y(x²+xy+y²) =x³+x²y+xy²-x²y-xy²-y³ =x³-y ³=LHS )**QUESTIONS**Factorize: i)27y³+125z³=(3y)³+(5z)³ =(3y+5z)[(3y)²-(3y)(5z)+(5z)²] =(3y+5z)(9y²-15yz+25z²) ii) 64m³-343n³=(4m)³-(7n)³ =(4m-7n)[(4m)²+(4m)(7n)+(7n)²] =(4m-7n)(16m²+28mn+49n²)**Identity VIII**x3 + y3+ z3-3xyz = (x + y + z)(x2 + y2 + z2– xy – yz – zx) Nowconsider(x + y + z)(x2+ y2 + z2– xy – yz – zx) On expanding, we get the product as x(x2 + y2 + z2– xy – yz – zx) + y(x2 + y2 + z2– xy – yz – zx) + z(x2 + y2 + z2– xy – yz – zx) = x3 + xy2 + xz2 – x2y – xyz – zx2 + x2y + y3 + yz2 – xy2 – y2z – xyz + x2z + y2z + z3 – xyz – yz2 – xz2 = x3 + y3+ z3-3xyz (On simplification)**QUESTIONS**Factorize: 27x³+y³+z³-9xyz =(3x)³+(y)³+(z)³-3(3x)(y)(z) =(3x+y+z)[(3x)²+(y)²+(z)²-(3x)(y)-(y)(z)-(z)(3x) =(3x+y+z)(9x²+y²+z²-3xy-yz-3zx)**QUESTIONS**If x+y+z=0,show that x³+y³+z³=3xyz SOLN: Since x+y+z=0 (given) LHS = x³+y³+z³=(x³+y³+z³-3xyz)+3xyz =(x+y+z)(x²+y²+z²-xy-yz-zx)+3xyz =(0)(x²+y²+z²-xy-yz-zx)+3xyz =0+3xyz =3xyz =RHS**QUESTIONS**Without actually calculating the cubes ,find the values of the following: (-12)³+(7)³+(5)³ SOLN: Let x=(-12) ,y=7 ,z=5 then,x+y+z=(- 12)+7+5= -12+12=0 we know that if x+y+z=0,then x³+y³+z³=3xyz (-12)³+(7)³+(5)³=3(-12)(7)(5) = -1260**ACTIVITY: interpret geometrically the factors of a quadratic**expression of the type ax²+bx+c (where a=1),using square grids.Take a=1 ,b=10 and c=21 to get the polynomial x 2 +10x +21 Take a square grid of dimension (10X10) which represents x2 [here x=10] . Find two numbers whose sum is 10 and product is 21 i.e.,7 and 3 . X X**Add 7 strips of dimensions x and 1 .Now the area of the**rectangle formed is x²+7x X X+7 7**X**3 Then add 3 strips of dimemsions x and 1 . Now the total area = (x2+7x)+3x X X 7**X**3 Add 21 small squares of dimension 1 and 1 to complete the rectangle .Now the area becomes X²+7X+3X+21 The area of rectangle =(x+3)(x+7) =x2+7x+3x+21 =x2+10x+21 X 7 x+7